2019
DOI: 10.3390/diagnostics9040198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Steatosis in Rodents by Time-Domain Nuclear Magnetic Resonance

Abstract: Devices that analyze body composition of rodents by time-domain nuclear magnetic resonance (TD-NMR) are becoming popular in research centers that study metabolism. Theoretically, TD-NMR devices can also evaluate lipid content in isolated tissues. However, the accuracy of TD-NMR to determine hepatic steatosis in the liver of small laboratory animals has not been evaluated in detail. We observed that TD-NMR was able to detect increased lipid content in the liver of rats consuming high-fat diet (HFD) for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Magnetic resonance imaging of body fat revealed that HFD-fed GIPR-Q350 mice have a lower fat mass and no change in lean mass as compared to GIPR-WT mice ( Figure 6B). Of note, the fat mass of HFD-fed GIPR-Q350 males, 16.6% of body weight, was comparable to values reported in the literature for fat mass of similarly aged WT mice fed a normal chow diet, ~16% of body mass (Pedroso et al, 2019;Sharma et al, 2019), demonstrating the near complete blunting of weight gain in GIPR-Q350 male mice on HFD.…”
Section: Gipr-q350 Males Are Resistant To Diet-induced Obesitysupporting
confidence: 82%
“…Magnetic resonance imaging of body fat revealed that HFD-fed GIPR-Q350 mice have a lower fat mass and no change in lean mass as compared to GIPR-WT mice ( Figure 6B). Of note, the fat mass of HFD-fed GIPR-Q350 males, 16.6% of body weight, was comparable to values reported in the literature for fat mass of similarly aged WT mice fed a normal chow diet, ~16% of body mass (Pedroso et al, 2019;Sharma et al, 2019), demonstrating the near complete blunting of weight gain in GIPR-Q350 male mice on HFD.…”
Section: Gipr-q350 Males Are Resistant To Diet-induced Obesitysupporting
confidence: 82%